Employee Perceptions of the Fraud Risk Triangle Factors Against Asset Misappropriation - Andriani, Ingka; Andy Lasmana; Ayi Jamaludin Aziz (Institut Bisnis dan Informatika Kesatuan, 2024)
Misappropriation of assets refers to unauthorized or inappropriate actions intheuse, handling, or processing of company assets. This study aims to identify the influence of pressure, opportunity, and rationalization on misappropriation of assets, both simultaneously and partially. The population for this study consisted of all employees in the Mechanical Department of PT XYZ, with a sample of 60 individuals selected using a saturated sampling technique or census from a non-probability sampling method. Data were collected by distributing questionnaires to the selected respondents. Data analysis was conducted using JASP software version 0.18.30. The results of the study indicate that pressure, opportunity, and rationalization have a significant influence on misappropriation of assets, both simultaneously and partially. Rationalization contributed significantly to the misappropriation of assets among employees of the Mechanical Department of PT XYZ, with these factors increasing the likelihood of unethical behavior.